2014
DOI: 10.1186/1756-0500-7-871
|View full text |Cite
|
Sign up to set email alerts
|

miRNome of inflammatory breast cancer

Abstract: BackgroundInflammatory breast cancer (IBC) is an extremely malignant form of breast cancer which can be easily misdiagnosed. Conclusive prognostic IBC molecular biomarkers which are also providing the perspectives for targeted therapy are lacking so far. The aim of this study was to reveal the IBC-specific miRNA expression profile and to evaluate its association with clinicopathological parameters.MethodsmiRNA expression profiles of 13 IBC and 17 non-IBC patients were characterized using comprehensive Affymetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…However, miR-548 in breast cancer have not been fully elucidated. miR-548h was reported that it was lower in inflammatory breast cancer [9]. Consistant with this result, miR-548-3p, as a remember of miR-548 family, we found its expression was also down-regulated in clinical specimens and in breast cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…However, miR-548 in breast cancer have not been fully elucidated. miR-548h was reported that it was lower in inflammatory breast cancer [9]. Consistant with this result, miR-548-3p, as a remember of miR-548 family, we found its expression was also down-regulated in clinical specimens and in breast cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…In 2, 3, 4, and 5 days of culturing, culture medium from one flask cultured simultaneously was collected and the cells were homogenized in QIAzol buffer (Qiagen). Total RNA was isolated from conditioned culture medium using miRNeasy Serum/Plasma Kit (Qiagen) with Ambion GlycoBlue Coprecipitant (15 mg/ml; Life Technologies) and from the cells using miRNeasy Mini Kit (Qiagen) as described previously [7,13].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, induction of miR-1296 was found to induce apoptosis in triple negative breast cancer [28]. Although the other miRNAs presented in Figure 5 have not yet been associated with metastasis per se, several have been linked to cancer more generally, including miR-423 which is found to promote tumour progression in laryngeal cancer [15], and miR-101-2 and miR-4687 which are found to be associated with gastric cancer [31] and breast cancer [25] respectively. Confirmatory studies are needed to determine whether these miRNAs promote oncogenesis through the regulation of genes predicted by our random forest model.…”
Section: Microrna As a Predictor Of Mrna Expressionmentioning
confidence: 99%